Analysis of the acoustic emission of a modified segment of a wind turbine blade with a NACA 0012 airfoil - Дреус, Андрій; Дербаба, Віталій; Гаркавенко, Дмитро; Алексєєнко, Сергій (Київський національний університет імені Тараса Шевченка, 2025)
The relevance of the study is due to the need to reduce the noise pollution that occurs during the operation of wind power plants, in particular, in densely populated or environmentally sensitive regions. One of the promising approaches to reducing the acoustic radiation of wind turbine blades is the modification of their geometry to control turbulent flow structures. This paper presents the methodology and results of an experimental study of aerodynamic noise generated by a NACA0012 blade profile. The effect of periodic notches on the trailing edge on the acoustic characteristics of the profile is studied. The aim of the work is to assess the effectiveness of the notched trailing edge in reducing the level of aerodynamic noise. The study was conducted in an anechoic chamber using physical models of the profile manufactured by 3D printing, and acoustic measurements were performed using a sound level meter with subsequent data processing using the Fast Fourier Transform (FFT) method. The experiments covered different incident flow velocities (from 10 to 20 m/s) and angles of attack (0° and 5°), and the results are presented in the form of sound pressure spectra. It was found that the modified profile provides a reduction in the sound pressure level of up to 7 dB compared to the standard profile. The effect is especially pronounced in the frequency range up to 8 kHz, typical of vortex noise sources at relatively low flow velocities. The proposed approach demonstrates high efficiency and can be applied to optimize the designs of wind turbines, as well as other rotating elements, such as UAV propellers or fans. Pages of the article in the issue: 95 - 100 Language of the article: Ukrainian

Актуальність дослідження зумовлена потребою зменшення шумового забруднення, що виникає під час експлуатації вітроенергетичних установок, зокрема в умовах густонаселених або екологічно чутливих регіонів. Одним із перспективних підходів до зниження акустичного випромінювання лопатей вітрових турбін є модифікація їхньої геометрії для контролю турбулентних структур потоку. У пропонованій роботі представлено методологію та результати експериментального дослідження аеродинамічного шуму, що генерується профілем лопаті типу NACA0012. Досліджено вплив періодичних зазубрин на задній крайці на акустичні характеристики профілю. Метою роботи є оцінка ефективності зазубреної задньої крайки у зниженні рівня аеродинамічного шуму. Дослідження проведено в безлунній камері з використанням фізичних моделей профілю, виготовлених методом 3D-друку, а акустичні вимірювання виконано за допомогою шумоміра з подальшим обробленням даних методом швидкого перетворення Фур'є (FFT). Експерименти охоплювали різні швидкості набігаючого потоку (від 10 до 20 м/с) і кути атаки (0° та 5°), а результати подано у вигляді спектрів звукового тиску. Встановлено, що модифікований профіль забезпечує зниження рівня звукового тиску до 7 дБ порівняно зі стандартним профілем. Ефект особливо виражений у частотному діапазоні до 8 кГц, характерному для вихрових джерел шуму за відносно низьких швидкостей потоку. Запропонований підхід демонструє високу ефективність і може бути застосований для оптимізації конструкцій вітрових турбін, а також інших обертових елементів, таких як пропелери БПЛА або вентилятори.
Аналіз акустичного випромінювання модифікованого сегмента лопаті вітрової турбіни з профілем NACA 0012
Keywords: aerodynamic noise; wind turbine; NACA0012 airfoil; serrated edge; experimental investigation; acoustic measurements; FFT; acoustic emission; аеродинамічний шум; вітрова турбіна; профіль NACA0012; зазубрена крайка; експериментальне дослідження; акустичні вимірювання; FFT; акустичне випромінювання